2014
DOI: 10.2134/jeq2013.12.0521
|View full text |Cite
|
Sign up to set email alerts
|

Stream Sediment Sources in Midwest Agricultural Basins with Land Retirement along Channel

Abstract: Documenting the effects of agricultural land retirement on stream-sediment sources is critical to identifying management practices that improve water quality and aquatic habitat. Particularly difficult to quantify are the effects from conservation easements that commonly are discontinuous along channelized streams and ditches throughout the agricultural midwestern United States. Our hypotheses were that sediment from cropland, retired land, stream banks, and roads would be discernible using isotopic and elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Streambank soils in retired systems (such as conservation reserve program) can also behave as long-term P sources to streams (Williamson et al, 2014).…”
Section: Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Streambank soils in retired systems (such as conservation reserve program) can also behave as long-term P sources to streams (Williamson et al, 2014).…”
Section: Soilsmentioning
confidence: 99%
“…Both studies concluded that streambanks represented a considerable source of P, and riparian forest sites showed significantly lower rates of retreat. Williamson et al (2014) used tracers to measure sediment contribution from upland soils and stream banks along the tributaries of West Fork Beaver Creek in Minnesota. The channelbed and suspended sediment was sampled and compared to the local sources that consisted of retired cropland, cropland, wetland and forest, grassland and pasture, and developed roads.…”
Section: Streambanks P Concentrations and Loadsmentioning
confidence: 99%
“…A good example is provided by postimplementation monitoring programs of agricultural land retirement (Christensen and Kieta ) and wetland restoration (Kreiling et al ) efforts in the upper Mississippi basin, which have demonstrated reductions in sediment and associated nutrient loading in adjacent waterways. Validation monitoring using isotopic and elemental tracers in suspended sediments demonstrated that cropland and stream bank soils accounted for a far greater proportion of sediments in streams lacking adjacent conservation actions (Williamson et al ). As sediment‐bound nutrient drainage and runoff into streams and rivers contribute to harmful algae blooms and hypoxic dead zones in receiving waters, validation of these conservation practices strengthens the case for their use to reduce agricultural runoff and its adverse effects.…”
Section: Designing and Implementing A Monitoring Planmentioning
confidence: 99%
“…On agricultural fields, high soil‐test P concentrations are evidence of legacy P (King et al., 2017) that is recycled and remobilized despite on‐field management efforts to decrease the delivery of new P to the stream system (Casillas‐Ituarte et al., 2020; Haygarth et al., 2012; Sandström et al., 2020; Sharpley et al., 2009, 2013; Smith et al., 2018, 2019; Stackpoole et al., 2019). Additional legacy P can come from stream sediment (Jarvie et al., 2013) and streambanks (Williamson, Dobrowolski, et al., 2020), contributing both suspended sediment (SS) and particulate P, especially during high‐streamflow conditions (Gellis & Noe, 2013; Gellis et al., 2019; van der Perk et al., 2007; Williamson et al., 2014). Depending on the characteristics of new SS (McDowell et al., 2020), in‐stream P dynamics may change as a function of equilibrium (i.e., [ad]sorption and desorption) between DP (James & Barko, 2004; Simpson et al., 2021) and particulate P (Owens & Walling, 2002), affecting the delivery of DP to Lake Erie (King et al., 2021).…”
Section: Introductionmentioning
confidence: 99%